Intermittent Femoral Nerve Block after Knee Arthroplasty for Assisting Physiotherapy - Mohamed, Abdul Hadi; Awang, Mohd Shukrimi; Abdullah, Nor Zamzila; Osman, Ariff (2009)
We report a case of intermittent femoral nerve block to assist in physiotherapy after knee arthroplasty. A 25-year-old factory worker sustained right anterior cruciate ligament tear after sport injury and had undergone a reconstructive surgery. One month after the operation, he developed arthrofibrosis and experienced severe pain with limited joint movement particularly during physiotherapy. He then underwent a second anterior cruciate ligament reconstruction followed by physiotherapy to increase the range of movement. In order to alleviate the pain during physiotherapy and ambulation process, we have introduced an intermittent femoral nerve block via catheter in situ. The technique has successfully relieved the pain and assisted him to tolerate the pain during the physiotherapy process until he reached full range of movement. We conclude that this technique is useful for post operative analgesia and helpful in to ease the pain during physiotherapy.